Camilla Erculiani, Letters on Natural Philosophy: The Scientific Correspondence of Sixteenth-Century Pharmacist with Related Text, edited by Eleonora Carinci, translated by Hannah Marcus, foreword by Paula Findlen, Iter Press, New York and Toronto 2021 - Scarlato, Chiara (Itinerari, 2023)